1971
DOI: 10.1080/00359197109519120
|View full text |Cite
|
Sign up to set email alerts
|

THE ECOLOGY OF THE SANDY BEACHES OF THE CAPE PENINSULA, SOUTH AFRICA PART 2: THE MODE OF LIFE OFBULLIA(GASTROPODA: PROSOBRANCHIATA)

Abstract: OPSOMMINC'n Verslag word gegee van ons kennis van die strandslak, Bullia, op die Kaapse Skiereilandstrande. Dit is vernaamlik die twee soorte, B. digitalis and B. rhodostoma, albei soorte wat lief vir die branding is, wat behandel word. Die B. laevissima, 'n soort wat voorkeur het vir kalm water, word ook vermeld. Die voortplantingsgedrag word vir die eerste keer beskrywe. Heelwat van die werk gaan oor chemoresepsie en die reaksies wat tot voedselopname lei. Sommige gevolgtrekkings word gemaak in verband met g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
10
0

Year Published

1978
1978
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…The right inset shows the current distribution of B. rhodostoma. The major marine biogeographic regions (Griffiths et al 2010) are indicated at the bottom of the figure; abbreviations are as follows: NMB  Namaqua Bioregion, SWCB  South-Western Cape Bioregion, AB  Agulhas Bioregion, NB  Natal Bioregion, DB  Delagoa Bioregion Numerous egg capsules, each with at least 150 eggs, are deposited 4-12 cm below the sand surface or on the ventral surface of the foot of the females (Brown 1971;da Silva and Brown 1985). Owing to their direct developmental mode, and because sandy beaches are interspersed with rocky shores, Bullia species are expected to exhibit high genetic differentiation across their geographic range.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The right inset shows the current distribution of B. rhodostoma. The major marine biogeographic regions (Griffiths et al 2010) are indicated at the bottom of the figure; abbreviations are as follows: NMB  Namaqua Bioregion, SWCB  South-Western Cape Bioregion, AB  Agulhas Bioregion, NB  Natal Bioregion, DB  Delagoa Bioregion Numerous egg capsules, each with at least 150 eggs, are deposited 4-12 cm below the sand surface or on the ventral surface of the foot of the females (Brown 1971;da Silva and Brown 1985). Owing to their direct developmental mode, and because sandy beaches are interspersed with rocky shores, Bullia species are expected to exhibit high genetic differentiation across their geographic range.…”
mentioning
confidence: 99%
“…The two-phase life cycle of Bullia species involves benthic eggs that undergo up to five weeks of lecithotrophic development to hatch directly (i.e. no planktonic phase) into miniature snails (Brown 1971;da Silva and Brown 1985 Figure 1: Sampling localities, oceanic currents, biogeographic regions, and directionality of gene flow between adjacent localities for Bullia rhodostoma on the South African coast. Arrows indicate the direction of gene flow and the thickness of an arrow is proportional to relative migration rate.…”
mentioning
confidence: 99%
“…Previous studies on the reproductive biology of rocky intertidal molluscs from southern Africa have been restricted to broadcast spawners (Newman 1967;Branch 1974;Griffiths 1977;Joska & Branch 1983;Lasiak 1986aLasiak & b, 1987a. With the exception of sandy beach whelks of the genus BuJlia (Brown 1971;McGwynne & van der Horst 1985) little is known of reproduction in gastropods which copulate and deposit egg capsules. The present study, based on gonadal histology, examines the gametogenic cycles of three numerically abundant internal fertilizers: the archaeogastropods Nerita albicilJa and Nerita plicata and the neogastropod Bumupena lagenaria.…”
mentioning
confidence: 99%
“…Plough shells of the genus Bullia are well represented on South African sandy shores with five intertidal and eight subtidal species (Brown 1971). They are carnivorous scavengers and feed on stranded organisms, particularly coelenterate medusae and siphonophores.…”
mentioning
confidence: 99%
“…They are carnivorous scavengers and feed on stranded organisms, particularly coelenterate medusae and siphonophores. Some aspects of the general biology and physiology of Bullia species in the Cape Peninsula have been studied by Brown (1961Brown ( , 1971. However, despite the quantitative importance of this group on South African sandy beaches (McLachlan 1977 b,c) there are no published data on population parameters such as growth and production.…”
mentioning
confidence: 99%